High population density in arracacha (Arracacia xanthorrhiza Bancroft) increase radiation interception, yield, and profitability = Densidad poblacional alta en arracacha (Arracacia xanthorrhiza Bancroft) aumenta la intercepción de la radiación, el rendimiento y la rentabilidad - Quevedo Amaya, Yeison Mauricio
Introduction. Arracacha (Arracacia xanthorrhiza Bancroft) a promising crop due to its nutritional and gastronomic relevance. Population density is an agronomic practice that increases water and radiation use efficiencies, maximizes the yield, and crop profitability. However, the selection of the optimal population density based on physiological, agronomic, and economic criteria for arracacha has not been studied. Objective. To describe the effect of different population densities on the physiology, yield, and profitability of arracacha. Materials and methods. The experiment was conducted in Cajamarca, Colombia in 2019. There, the soil water potential, relative chlorophyll content, photosynthesis, stomatal conductance, water use efficiency, leaf temperature depression, photosynthetic reflectance index, leaf area index, the fraction of light interception, light extinction coefficient, cracking index, yield, and profitability were evaluated. Results. The results showed that high population densities did not generate water deficit because there were no significant differences for the soil water potential, leaf temperature depression, and photosynthetic reflectance index. Furthermore, no nutritional deficiencies were evidenced because the relative chlorophyll content (<32 SPAD) was higher at the critical level. Due to this, no limitations were observed in leaf gas exchange processes. However, the densities of 25,000 and 30,000 plants ha-1 showed a higher fraction of light interception due to the increase in the leaf area index; this allowed to obtain a higher yield at these densities. Conclusion. The maximum yield (41.96 t ha-1) and profitability (US$ 15,333.06 ha-1) were reached with a population density of 22,222 plants ha-1.